Analisis Cabang Ilmu Kebahasaan Buku Ajar Jenjang Sekolah Dasar - Amira Rizqun Malakiano; Reni Putri Hapsari; Fadlillah Nurul Aini; Adhelia Novian Putri (Jurnal Edukasi, 2026)
This study examines linguistic disciplines including morphology, syntax, semantics, and pragmatics using the Systematic Literature Review (SLR) method. The instruments employed are several textbooks aligned with the Merdeka Curriculum. The primary objective is to analyze these textbooks as key tools for understanding how various linguistic aspects are integrated and presented in learning materials. Through the SLR approach, this research collects and synthesizes relevant literature sources on the application of morphology, syntax, semantics, and pragmatics theories. The findings are expected to provide a comprehensive overview of the representation and role of these four aspects in language education.